1979
DOI: 10.1021/ac50049a046
|View full text |Cite
|
Sign up to set email alerts
|

Rotating-ring-disk analysis of iron tetra(N-methylpyridyl)porphyrin in electrocatalysis of oxygen

Abstract: Future efforts involving the technique presented here will involve improvement of resolution using a smaller slit, improvement in alignment between slit and electrode, and the use of diffracted light to examine events close to the electrode. In its present form, the technique allows direct observation of concentrations of electroactive materials as a function of both time and distance with unprecedented sensitivity and selectivity. The long pathlength, selectivity gained from wavelength selection, and spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(38 citation statements)
references
References 13 publications
0
38
0
Order By: Relevance
“…6 C and D). In particular, the 830-cm −1 band, which gains intensity in 16 O 2 buffer (Fig. 6 A and C), loses intensity in the 18 O 2 -saturated buffer (Fig.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…6 C and D). In particular, the 830-cm −1 band, which gains intensity in 16 O 2 buffer (Fig. 6 A and C), loses intensity in the 18 O 2 -saturated buffer (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Both natural systems [metalloenzymes such as cytochrome c oxidase (CcO), hydrogenase, and glucose oxidase] and biomimetic systems (i.e., synthetic/biochemical mimics of the natural enzyme) are known to function as electrocatalysts (12)(13)(14)(15). In particular, it has been known for five decades that heme/porphyrin-based electrocatalysts (both natural and synthetic) catalyze electrochemical O 2 , H + , and CO 2 reduction (14,(16)(17)(18)(19). Several excellent metalloporphyrin-based O 2 reduction electrocatalysts have been reported, some mimicking natural active sites and some inspired by their design (14,20).…”
mentioning
confidence: 99%
“…dissociation 1501, or dismutation [51] of adsorbed 0,H). It has been found that in many, though not all, cases 0, reduction is associated with the (presumably) Me"/Me"' redox transition in the adsorbed or attached chelate [49,[52][53][54][55][56][57][58][59]. Unfortunately it has not been possible to study the Me"/Me"l redox process in our catalysts by cyclic voltammetry or differential pulse polarography owing to the high background currents of the active carbon support.…”
Section: Potential Of the Central Metal Ionmentioning
confidence: 99%
“…The oxygen reduction reaction with metalloporphyrins as electrocatalysts has been extensively studied [116][117][118][119][120][121][122][123]. It was shown that porphyrins have high electrocatalytic activity toward the ORR.…”
Section: Oxygen Reduction Using Carbon Electrodes Modified With Metalmentioning
confidence: 99%
“…two for all four CoPPx and therefore it was concluded that on glassy carbon electrodes modified with CoPPx, the oxygen reduction reaction proceeds through two-electron process to hydrogen peroxide. Also, the electrogenerated ferrous form of iron tetrakis (M-methyl-4-pyridyl) porphyrin (bisulfate) has been shown to be an effective catalyst for the reduction of oxygen to hydrogen peroxide via two-electron pathway [117][118][119]127]. On the other hand, the reduced form of iron tetrakis (M-methyl-4-pyridyl) porphyrin, electrogenerated at a highly polished glassy carbon electrode has showed catalytic activity for electrochemical reduction of oxygen to water via a multistep mechanism [116].…”
Section: Oxygen Reduction Using Carbon Electrodes Modified With Metalmentioning
confidence: 99%